Potential Benefits of Exercise on Blood Pressure and Vascular Function - Pal, Sebely; Radavelli-Bagatini, Simone; Ho, Suleen (Elsevier Inc., 2013)
Physical activity seems to enhance cardiovascular fitness during the course of the lifecycle, improve blood pressure, and is associated with decreased prevalence of hypertension and coronary heart disease. It may also delay or prevent age-related increases in arterial stiffness. It is unclear if specific exercise types (aerobic, resistance, or combination) have a better effect on blood pressure and vascular function. This review was written based on previous original articles, systematic reviews, and meta-analyses indexed on PubMed from years 1975 to 2012 to identify studies on different types of exercise and the associations or effects on blood pressure and vascular function. In summary, aerobic exercise (30 to 40 minutes of training at 60% to 85% of predicted maximal heart rate, most days of the week) appears to significantly improve blood pressure and reduce augmentation index. Resistance training (three to four sets of eight to 12 repetitions at 10 repetition maximum, 3 days a week) appears to significantly improve blood pressure, whereas combination exercise training (15 minutes of aerobic and 15 minutes of resistance, 5 days a week) is beneficial to vascular function, but at a lower scale. Aerobic exercise seems to better benefit blood pressure and vascular function.